Metastatic chondroblastoma (Faculty of Medicine Universitas Indonesia, 2001)
A case of chondroblastoma, which is a benign tumor of the bone, with distant metastases to the lung and abdominal wall is reported. The clinical course of the disease was progressive like that of malignant process. (Med J Indones 2001; 10:57-9) Keywords : chondroblastoma, bone tumor